Pengaruh Budaya Organisasi, Lingkungan Kerja dan Work Family Conflict Terhadap Kinerja Karyawan Hotel The Madeline Kota Bengkulu - Darti Darti; Merta Kusuma (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of organizational culture, work environment, work family conflict on employee performance at The Madeline Hotel Bengkulu City, either partially or simultaneously. There are several factors that will be discussed in this study, including the work environment organizational culture and work family conflict. The object of this research is the Hotel The Madeline, Bengkulu City, with a total of 55 people. In this research, the writer uses the method of collecting data by means of observation, interviews and questionnaires. There are several data analysis techniques used in this study, using instrument tests, namely validity test, reliability test, classical assumption test, coefficient of determination, and also hypothesis testing. From the results of multiple linear regression, the regression equation is as follows: Y = 9.369 + 0.622(X1) + 0.101(X2) + 0.193(X3). Meanwhile, the results of the hypothesis testing that have been carried out can be seen that the Organizational Culture variable (X1) obtained tcount of 5.320 (higher than the ttable value, or tcount > 1.67 (see distribution in table t), and a significance level of 0.000 (significant < 0.05) Work Environment Variable (X2) obtained tcount of 1.006 (lower than ttable value, or tcount < 1.67 (see distribution in table t), and significance level of 0.319 (significant > 0.05) and Work Family Conflict variable (X3 ) obtained tcount of 1.719 (lower than the value of ttable, or tcount > 1.67 (see distribution in table t), and a significance level of 0.092 (significant > 0.05). So it can be concluded that the hypothesis is accepted, meaning that there is an effect either partially or simultaneously between Organizational Culture (X1), Work Environment (X2) and Work Family Conflict (X3) on the Employee Performance variable (Y).This can be seen at a significance level of 0.000 <0.05 in The Madelin Hotel, Bengkulu City.